Financial Development and Micro-Entrepreneurship - Dehejia, Rajeev; Gupta, Nandini (Journal of Financial and Quantitative Analysis, 2022)
Abstract Does financial development facilitate micro-entrepreneurship? Using randomized surveys of over 1 million Indian households and bank-branch location as predetermined by government policy, we find that access to finance shifts workers from informal micro-entrepreneurship into formal employment. Financial access reduces the likelihood of being self-employed but benefits micro-enterprises with employees, as well as formal firms. Using data on 400,000 firms, we find that in districts with more banks, firms have higher loans, productivity, employment, and wages than firms in less banked districts. This evidence suggests a labor-market mechanism by which financial development facilitates growth: by shifting workers from unproductive micro-entrepreneurship into productive employment.